Influence of Parameters on the Pre-Reduction Process of Vanadium-Titanium Magnetite Carbon-Containing Composite Pellets in Rotary Kiln - Bo Wang; Xueyong Ding; Tianhua Ju; Xiaofei Zhang; Gongjin Cheng (Metals, 2020)
A novel smelting reduction process called pre-reduction in rotary kiln and total oxygen melting pool is a promising route to reduce environmental pollution from the ironmaking industry. In this paper, the process parameters and appropriate efficiency of reduction in the pre-reduction process of the rotary kiln were investigated via the detection of the metallization rate, phase composition, and internal morphology of the product combining with the analysis of the off-gas. The results indicated that the parameters of reduction temperature, reduction holding time, and coal ratio have a remarkable influence on the metallization rate. The reduction temperature has the most significant effect, followed by the reduction time and the coal ratio. Furthermore, under the condition of reduction temperature 1000 °C, holding time 30 min, coal ratio = 1, a product with a metallization rate of more than 70% can be obtained, which meets the requirements of the rotary kiln process, and its CO2/CO value of the pre-reduction endpoint is appropriate. Continue to increase the temperature, holding time, and coal ratio can raise the metallization rate of the pellets, but only a little improvement and may cause reoxidation of the product.